2020
DOI: 10.3126/arj.v1i1.32456
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Cytotoxic and Antioxidant Activity of Alternathera sessilis and Moringa oleifera

Abstract: Methanol and hexane extracts of leaves of Moringa oleifera and aerial parts of Alternanthera sessilis were screened for the presence of different classes of phytoconstituents. Phytochemical screening revealed the presence of alkaloids, flavonoids, carbohydrates, terpenoids, polyphenols, glycosides, and coumarins in methanol extracts. Volatile oils, quinines, and phytosterols were absent in all extracts and saponins were present in all extracts. The biological activity of all the extracts was tested by performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…ex DC. for the management of cancer: Jain and the team had used the methanolic extract of leaves ( Jain et al, 2016 ); Firdhouse and Lalitha had used silver nanoparticles of the aqueous extract ( Firdhouse and Lalitha, 2013 ); Qian and the team had used gold nanoparticles of the aqueous extract of leaves ( Qian et al, 2019 ); D Suganya and the team had used aqueous extract of leaves and stems ( Suganya et al, 2019 ); Pathak and the team had used n-hexane and methanolic extracts of aerial parts ( Pathak et al, 2020 ); Mohaimenul and the team had used ethanolic extract of aerial parts ( Mohaimenul et al, 2020 ); Yap and the team had used ethanolic, 70% ethanolic, 80% methanolic, ethyl acetate, and aqueous extracts of the whole plant ( Yap et al, 2019 ); Sathishkumar and the team had used silver nanoparticles of the aqueous extract of leaves ( Sathishkumar et al, 2016 ); Arulselvan and the team had used ethanolic extract of aerial parts, stem, and leaves ( Arulselvan et al, 2018 ); while Guerra and the team aqueous extract of aerial parts ( Guerra et al, 2003 ). All these studies indicated the true potential of Alternanthera sessilis (L.) R.Br.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ex DC. for the management of cancer: Jain and the team had used the methanolic extract of leaves ( Jain et al, 2016 ); Firdhouse and Lalitha had used silver nanoparticles of the aqueous extract ( Firdhouse and Lalitha, 2013 ); Qian and the team had used gold nanoparticles of the aqueous extract of leaves ( Qian et al, 2019 ); D Suganya and the team had used aqueous extract of leaves and stems ( Suganya et al, 2019 ); Pathak and the team had used n-hexane and methanolic extracts of aerial parts ( Pathak et al, 2020 ); Mohaimenul and the team had used ethanolic extract of aerial parts ( Mohaimenul et al, 2020 ); Yap and the team had used ethanolic, 70% ethanolic, 80% methanolic, ethyl acetate, and aqueous extracts of the whole plant ( Yap et al, 2019 ); Sathishkumar and the team had used silver nanoparticles of the aqueous extract of leaves ( Sathishkumar et al, 2016 ); Arulselvan and the team had used ethanolic extract of aerial parts, stem, and leaves ( Arulselvan et al, 2018 ); while Guerra and the team aqueous extract of aerial parts ( Guerra et al, 2003 ). All these studies indicated the true potential of Alternanthera sessilis (L.) R.Br.…”
Section: Introductionmentioning
confidence: 99%
“…ex DC. : Borah and the team had used 90% methanolic, 70% acetone, 80% ethanolic extracts of leaves and stems ( Borah et al, 2011 ); Chai and the team had used hexane, chloroform, ethyl acetate, butanolic, and aqueous fractions of leaves and callus methanol extracts ( Chai et al, 2016 ); Sharma and the team 30% hydroethanolic extract of the whole plant ( Sharma et al, 2013 ); Khan and the team had used separate Methanolic and hexane extracts of leaves and stems ( Khan et al, 2018 ); Azizah and the team had used ethanolic and aqueous extracts of aerial parts ( Azizah et al, 2015 ); Muniandy and the team had used 90% hydroethanolic extract of stem ( Muniandy et al, 2018b ); Othman and the team had used ethanolic and aqueous extracts of aerial parts ( Othman et al, 2016 ); Tiwari and the team had used juice ( Tiwari et al, 2013 ); Rajamurugan and the team had used ethanolic extract of leaves ( Rajamurugan et al, 2013 ); Jain and the team had used methanolic extract of leaves ( Jain et al, 2016 ); Suganya and the team had used aqueous extract of leaves and stems ( Suganya et al, 2019 ); Mohd Hazli and the team had used hexane, ethyl acetate, ethanolic, and aqueous extracts of leaves and stem ( Mohd Hazli et al, 2019 ); Niraimathi and the team had used silver nanoparticles from aqueous extract of leaves ( Niraimathi et al, 2013 ); Yap and the team had used 100% ethanolic, 70% ethanolic, 80% methanolic, ethyl acetate, and aqueous extracts of the whole plant ( Yap et al, 2019 ); Kota and the team had used petroleum ether, ethyl acetate, chloroform, and methanolic extract of leaves ( Kota et al, 2017 ); Sundar and the team had used petroleum ether and methanolic extracts of leaves ( Sundar et al, 2019 ); Pathak and the team had used n-hexane and methanolic extracts of aerial parts ( Pathak et al, 2020 ); Khan and the team had used the volatile oil of leaves and flowers ( Khan et al, 2016 ); while Salvador and the team had used ethanolic extract and its four fractions; Acacetin 8-c-[ α -L-rhamnopyranoyl-(1→2)- β -D-glucopyranoside]; 2″- O -α-L-rhamnopyranosyl-vitexin; 2″- O - β -D-glucopyranosyl vitexin and Vitexin ( Salvador et al, 2006 ). Results from these researches left no doubt in the credibility and applicability of Alternanthera sessilis (L.) R.Br.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthine oxidase inhibitory assay is considered as standard to study the anti gout potential of medicinal plants. Some plants and their phytochemicals can act as xanthine oxidase inhibitors [34,35]. The phytochemical screening of Alternanthera sessilis and Moringa oleifera also revealed the presence of various phytonutrients.…”
Section: Resultsmentioning
confidence: 99%
“…The previous study revealed the presence of strong antioxidant potential in both Moringa oleifera and Alternanthera sessilis extract [34]. Xanthine oxidase inhibitory activity was observed for the extracts and compared with the standard drug allopurinol.…”
Section: Alternanthera Sessilis Moringa Oleiferamentioning
confidence: 89%
“…The difference in the growth inhibitory effect between the crude extracts is probably due to the different content of compounds in the different medicinal plant species (Ganga Rao et al, 2012;Missau et al, 2014;Alsultan et al, 2016;Lalitha et al, 2017;Khoo et al, 2018;Pathak et al 2020;Syed et al, 2020;Ove et al, 2021;Wuryatmo et al, 2021). Flavonoids, alkaloids and tannins are frequently reported from the extracts of the nine medicinal plant species (Ganga Rao et al, 2012;Salome et al, 2012;Alsultan et al, 2017;Bhagyasri et al, 2017;Johri and Khan, 2017;Ayirezang et al, 2020;Syed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%